School-work transition: the interplay between institutional and individual processes - Graaf, Willibrord de [Verfasser]; Zenderen, Kaj van [Verfasser] (My University, 2013)
"This study examines how problems with the transition from school to work, such as early school leaving and youth unemployment, are dealt with in the Dutch vocational education and training (VET) system. School-work transition has become more complex and fragmented with more room for individual manoeuvring. This leads to a more individualised perspective on school and labour market outcomes and on the reasons for transition failures. However, at the same time, the transition is still shaped by structural factors such as how the VET system and the labour market are organised. Our quantitative and qualitative empirical studies on VET schools confirm this tendency towards individualisation: professionals, including teachers, generally ascribe school failure to individual problems such as psychosocial problems or choosing the wrong course of study. The students themselves actually reinforce this, and display a strong belief in individual agency and feel in charge of their own learning and labour market outcomes. Structurally established barriers such as early selection mechanisms and ineffective school reforms do not interfere with this perception of individual strengths and failures." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 1.3.3 Vollzeitschulische Berufsausbildung; I 2.2.1 Westeuropa; Berufseinmündung; Zweite Schwelle; Schulische Berufsausbildung; Ausbildungsabbruch; Berufsbildungssystem; Niederlande